2020
DOI: 10.1111/1475-4932.12576
|View full text |Cite
|
Sign up to set email alerts
|

The Direction and Intensity of China’s Monetary Policy: A Dynamic Factor Modelling Approach*

Abstract: The recent update of the People’s Bank of China’s monetary policy framework establishes a corridor system of interest rates. We employ a dynamic factor modelling approach to derive an indicator of China’s monetary policy stance. The approach is based on the notion that co‐movements in several monetary policy instruments have a common element that can be captured by a single underlying, unobserved component. To clarify and interpret the derived index, we employ a baseline dynamic stochastic general equilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The Standing Lending Facility (SLF) instrument introduced in 2013, which is the upper limit for fluctuations in interbank offered rates, allows to provide liquidity 24 M. Funke, A. Tsang [2019], The direction and intensity of China's monetary policy conduct: a dynamic factor modelling approach, "The Bank of Finland Institute for Economies in Transition. Discussion Papers", vol.…”
Section: Mmentioning
confidence: 99%
“…The Standing Lending Facility (SLF) instrument introduced in 2013, which is the upper limit for fluctuations in interbank offered rates, allows to provide liquidity 24 M. Funke, A. Tsang [2019], The direction and intensity of China's monetary policy conduct: a dynamic factor modelling approach, "The Bank of Finland Institute for Economies in Transition. Discussion Papers", vol.…”
Section: Mmentioning
confidence: 99%
“…The rediscount rate used by the People's Bank of China (PBoC) remained constant after December 2010, while the monetary policy stance was steered through such measures as adjusting the size of open-market operations and the rate of the standing lending facility (see e.g. Funke and Tsang, 2019). Second, Ln(Balance sheet total / Consumer Price Index) measures the size of operations.…”
Section: Ch4)mentioning
confidence: 99%
“…In recent decades, China has gradually changed its monetary policy framework from a repressive financial system to a more market-based system (Funke and Tsang, 2021). The existing literature has shown that China's monetary policy has been tracking the Chinese economy well (see Funke and Tsang, 2021;Kamber and Mohanty, 2018;Sun, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, China has gradually changed its monetary policy framework from a repressive financial system to a more market-based system (Funke and Tsang, 2021). The existing literature has shown that China's monetary policy has been tracking the Chinese economy well (see Funke and Tsang, 2021;Kamber and Mohanty, 2018;Sun, 2018). In addition, Funke and Tsang (2020) have shown that China's swift and decisive monetary policy easing since the COVID-19 outbreak has supported the quick rebound of the economy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation